2015
DOI: 10.1007/s12298-015-0305-3
|View full text |Cite
|
Sign up to set email alerts
|

Hsp transcript induction is correlated with physiological changes under drought stress in Indian mustard

Abstract: Brassica juncea is an important oilseed crop and drought stress is major abiotic stress that limits its growth and productivity. RH0116 (drought tolerant) and RH8812 (drought sensitive) genotypes were undertaken to study some of the physiological parameters and hsp gene expression related to stress tolerance under drought stress conditions. Differential response in terms of seed germination, electrolyte leakage, RWC, osmotic potential was observed in the selected genotypes. In vitro seed germination studies us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Increased expression of NADH ubiquinone oxidoreductase and induction of P450 genes were involved in resistance to pyriproxyfen insecticide in Bemisia tabaci [ 123 ]. Induction of heat shock proteins is associated with drought and oxidative stress in Brassica juncea [ 124 ] and A . thaliana [ 125 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of NADH ubiquinone oxidoreductase and induction of P450 genes were involved in resistance to pyriproxyfen insecticide in Bemisia tabaci [ 123 ]. Induction of heat shock proteins is associated with drought and oxidative stress in Brassica juncea [ 124 ] and A . thaliana [ 125 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…vannamei , the HSPs were detected as the main expressed genes among the major immune factors, and two HSP70 family genes (HSPA8 and HSPA4) were discovered as the hub regulation genes in the PPI networks. The key role of HSP70s had been proved involving in response to various stressful stimuli in previous studies [124125]. The results of Duan et al (2018) showed that the expression of HSP70 increased to the highest level by exposing the L .…”
Section: Discussionmentioning
confidence: 98%
“…The transcript levels of bHLH122 were strongly induced by drought, and up-regulation of bHLH122 substantially increased cellular ABA levels, which demonstrated that bHLH122 functions as a positive regulator of water-deficit conditions (Liu et al, 2014). Heat shock proteins (HSPs) are induced by drought and correspond to enhanced tolerance (Aneja et al, 2015). Previous studies found that overexpression of HSP17.6A in Arabidopsis resulted in gain of tolerance in these plants during water-deficit conditions, possibly through protein stabilization (Sun et al, 2001).…”
Section: Discussionmentioning
confidence: 99%